Subdural hematomas and medical malpractice in the USA: an analysis of 314 patients - Isabella L Pecorari; Sayak Ghosh; Anne Lally; Vijay Agarwal (Trauma Surgery & Acute Care Open)
Introduction Subdural hematomas (SDHs) are a serious condition that can lead to high rates of morbidity and mortality. Given the prevalence of malpractice in healthcare, particularly among physicians who treat patients with high-risk conditions, the aim of this study was to analyze factors that impact litigation outcomes in cases pertaining to SDH.Methods The online legal database, Westlaw Edge, was used to identify cases related to malpractice and SDH between 1977 to 2023. Plaintiff demographics, geographic location, defendant specialties, reason for litigation, and trial outcomes were obtained.Results Three hundred and fourteen cases were included in the analysis. The most common reason for litigation was negligent care in a healthcare setting resulting in SDH (55.4%), followed by failure to diagnose (47.1%). Trauma (74.8%) was the most common cause of SDH. The most frequently cited defendants were emergency medicine physicians (76.4%). Most cases ended in a jury verdict in favor of the defense (64.5%). The only factor that was associated with a significantly higher rate of plaintiff compared with defendant verdicts was premature hospital discharge (p=0.007). The mean settlement was $658 741.65, whereas the mean plaintiff verdict payment was $4402 261.63.Conclusion Emergency medicine physicians are the most likely specialty to be sued in cases of SDH. Failure to diagnose and negligent care resulting in a subdural bleed are the most common reasons for litigation pertaining to this condition. Juries are more likely to return a verdict in favor of the defense. However, settlements are often less costly for defendants in comparison to the payouts of cases that were ruled in favor of the plaintiff.